Mangkir Kerja Dalam Perspektif Undang-Undang No 21 Tahun 2000 Tentang Serikat Pekerja/Serikat Buruh Hubungannya Dengan Undang-Undang No 13 Tahun 2003 Tentang Ketenagakerjaan - ., Bakar (CV. ITTC INDONESIA, 2024)
The recent labor incident is an iceberg phenomenon, namely workers' problems that are visible only on the surface, but the root causes of the problems are quite numerous and very unique. In the event that there is a disturbance or disturbance in the working relationship between the entrepreneur and the worker, the settlement will be resolved based on Law Number 2 of 2004 concerning Settlement of Industrial Relations. In this research, the author uses a normative juridical approach, namely a method that uses secondary data sources, namely statutory regulations, legal theory and the opinions of legal experts, which are then analyzed and draw conclusions from the problem that will be used to test and study secondary data. the. In problems that occur in the realm of employment, settlements usually occur between workers and entrepreneurs/employers and trade unions/labor unions and employers/employers. There are 4 (four) types of disputes, namely: Rights Disputes, Interest Disputes, Employment Termination Disputes and Disputes Between Trade Unions/Labour Unions Within One Company. The settlement can be resolved using litigation and non-litigation, non-litigation methods, namely by Bipatrit, Mediation, conciliation and arbitration.